5' flanking sequence and genomic structure of Egr-1, a murine mitogen inducible zinc finger encoding gene. - Tsai-Morris, C H (1988)
Egr-1 is a murine zinc finger encoding cDNA whose expression is modulated by a variety of ligand-receptor interactions and is often coregulated with c-fos (1). This study reports the isolation of a mouse Egr-1 genomic clone, its intron-exon structure, and 935 bp of 5' flanking sequence. The gene spans about 3.8 kb and consists of 2 exons and one 700 bp intron. S1 nuclease protection and primer extension analysis were used to define the transcription initiation site. "TATA" and "CCAAT" sequences were located at nucleotides -26 and -337 respectively. In addition, there exist five elements whose sequence is nearly identical to the inner core 10 nucleotide region (CCATATTAGG) of the c-fos serum response element, four Sp1 consensus sequences, two AP1 target sequence analogs, and two potential cAMP response elements. These results will ultimately lead to a detailed definition of the intracellular events regulating Egr-1 expression.